Analisa Desain dan Perancangan Ruang Vakum Medium Sebagai Media Pembangkitan Plasma Oksigen Menggunakan Gelombang Mikro 2,45 GHZ - Antonius Prisma Jalu Permana; Danang Murdiyanto; Bernardus Crisanto Putra Mbulu (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2020)
In line with the development of thin-film technology, its also developing plasma-based removal techniques such as plasma ashing. Plasma is an ionized gas-like phase. Ionized gas when the temperature approaches or exceeds atomic ionization energy. The atoms are ionized into positive and negative ions. The purpose of this research to analyze the working system of plasma generation using 2,45GHz microwaves. The plasma reactor was successfully operating, but it only maintain to generate plasma in short time. The reactor broke because it couldn’t hold the bombardment energy of particles which the energy was 1,623x10-24 for each every second. At last, the reactor could maintain the plasma only for ±240 s. Keywords: microwave, plasma, ashing, vacuum, mean free path, ionization.